Google sites as a media for promoting dental health in increasing knowledge in high school children - Reza Septiana; Eka Anggreni (Center of Excellent (Pusat Unggulan Iptek), 2023)
Background: Efforts to overcome dental and oral health problems can mostly be prevented by providing dental and oral health education. Times change, of course the perspective and way of learning of students is automatically different from before. In the past, they still used the lecture method using makeshift media. One of the learning media that can support and overcome these problems is Google Sites. Objective: To analyze effectiveness of the level of knowledge about dental and oral health maintenance before and after being given counseling using Google sites media for class X students of Husada Pratama Health Vocational School, Serang City in 2023. Methods: The type of research used in this study was a quasy experiment with a pretest and posttest design with one group design. The technique used in this study is the total sampling technique, which uses the entire population as a sample. Independent variable: google sites and dependent variable: dental health knowledge. data collection instrument using a questionnaire. Results: The results of this study show that the average value of knowledge about maintaining dental and oral health in class X students of SMK Kesehatan Husada Pratama Serang City before being given counseling using Google Sites media is 11.8 and after being given counseling with Google Sites media is 13 .5 with good category. Conclusion: there is an increase in knowledge about maintaining dental and oral health in students before being given counseling and after being given counseling using Google Sites media.